Nomadic livelihood resilience through tourism - Fatemeh Shekari; Mahmood Ziaee; Abolhassan Faghihi; Mahmoud Jomehpour (Annals of Tourism Research Empirical Insights, 2022)
In recent decades, global changes have resulted in tensions in socio-ecological systems. As a result, livelihood resilience has become a serious concern for managers and researchers. These changes had a negative impact on the livelihood resilience of Iran's nomadic communities. This study seeks to explore how tourism development affects the resilience of nomadic livelihoods. In this qualitative field research, we studied four nomadic communities living in the Fars province of Iran. The data was collected through semi-structured interviews with different informants, informal discussions, and field observations and then analyzed thematically. The findings demonstrate that tourism development strengthens nomadic livelihood resilience through improving the multifunctional quality of livelihood capitals and decreasing nomadic livelihood's reliance on animal husbandry by diversifying income sources.
Keywords: 330; Fars province; Iran; Livelihood resilience; Local communities; Nomadic tourism; Thematic analysis